(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study aims to investigate how political parties in India have used and expanded their usage of social media platforms as a means of conducting their election campaigns. Social media has emerged as a powerful tool for campaigns in India’s electoral system. Voters, particularly the millennial and Gen Z generations, are being courted by these new media platforms. Campaigns and political parties may more quickly and easily contact a huge number of people using social media. Unlike with more conventional forms of advertising, politicians may have two-way conversations with prospective voters on social media. Through the use of social media, political parties and candidates are able to directly communicate with voters, allowing them to feel more invested in the campaign by sharing their values, objectives, and achievements. By using social media, politicians may provide their supporters with an inside look into their campaign and make it easier to monitor activity. New media also makes it easier to gather news that is relevant to key audiences. It is crucial to do research due to the substantial increases in the usage and growth of social media. The purpose of this study is to examine the public’s engagement in politics as it relates to the usage and growth of social media platforms.